Distribution and generative mechanisms of ground fissures in China. (15th April 2020) - Peng, Jianbing; Qiao, Jianwei; Sun, Xiaohan; Lu, Quanzhong; Zheng, Jianguo; Meng, Zhenjiang; Xu, Jishan; Wang, Feiyong; Zhao, Junyan
Highlights: Ground fissures in China are mainly distributed in North China. The spatial distribution of ground fissures in China exhibits six regular patterns. Ground fissures in China are the result of internal and external dynamic coupling. Tectonic dynamics, local stress, and hydrodynamic expansion cause ground fissures. Abstract: In this study, 5002 ground fissures in more than 1500 localities across 22 provinces in China are investigated and mapped to reveal their spatial distribution. The distribution of these ground fissures in China exhibits six regular patterns – assemblages in North China, syngenesis in extensional basins, clustering along fault zones, distributing along geomorphic boundaries, developed on the edge of subsidence areas, and clustering in large and medium-sized cities. Combined with regional GPS, numerical simulations, physical model test and In-SAR monitoring, the generative processes of ground fissures are analyzed and discussed in relationship to four mechanisms: (1) deep dynamic tectonism controls on the location of ground fissures, (2) intracontinental dynamic tectonism resulting in ground fissure assemblages, (3) fault stress inducing formation of ground fissures, and (4) groundwater overmining resulting in the reactivation and expansion of ground fissures. The geological environment is thus responsible for the establishment and appearance of ground fissure. More importantly, ground fissure propagation in China is the result of the synergistic effects of internal geological dynamic (including in deep tectonism, intracontinental tectoniim, and fault movement) coupled with anthropomorphic stress. This genetic model can be summarized as one that is tectonically controlled, stress-driven, and affected by regional hydrodynamic.